2021
DOI: 10.1186/s12879-021-05836-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of self-reported correct knowledge about tuberculosis transmission among men and women in Malawi: evidence from a nationwide household survey

Abstract: Background Correct knowledge about transmission of tuberculosis (TB) can influence better health-seeking behaviors, and in turn, it can aid TB prevention in society. Therefore, this study aimed to examine the prevalence and predictors of self-reported correct knowledge about TB transmission among adults in Malawi. Methods We conducted a secondary analysis of the data obtained from the Malawi Demographic and Health Survey, 2015/16 (MDHS 2015/16). Qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In our study, we observed that the older age group had a better understanding of TB transmission modes compared to the late adolescent group, which is consistent with studies conducted in Malawi and India [12,17,18]. This finding can be attributed to the accumulation of life experiences and exposures among older individuals, which likely contributes to their improved knowledge and behaviors related to the disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, we observed that the older age group had a better understanding of TB transmission modes compared to the late adolescent group, which is consistent with studies conducted in Malawi and India [12,17,18]. This finding can be attributed to the accumulation of life experiences and exposures among older individuals, which likely contributes to their improved knowledge and behaviors related to the disease.…”
Section: Discussionsupporting
confidence: 89%
“…Studies conducted in Bangladesh and Ethiopia reported unsatisfactory levels of correct knowledge on TB transmission with 67% and 70% respectively [9,10]. Inadequate knowledge of TB transmission has been identified as a major barrier to disease prevention, early diagnosis, and treatment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there were 969,000 TB cases in Indonesia in 2021 according to the Global TB report 2022, and 44% were found in the most populous regions, including East, West, and Central Java. 4 Several factors cause TB cases to soar continuously, including the presence of Coronavirus disease (COVID- 19), nonadherence to treatment, and lack of public understanding. [5][6][7] Additionally, in low-middle-income nations, where TB remains prevalent, there are inadequate healthcare services, limited drug supply, not diagnosed/underdiagnosed cases, and a lack of reporting of suspected cases by the community due to insufficient information, all of which contribute to an increase in TB cases.…”
Section: Introductionmentioning
confidence: 99%
“…11 Continuing education processes are required to sustain the community's knowledge and behavior regarding TB. [14][15][16][17] Some studies have elucidated certain sociodemographic variables that are linked to the knowledge, attitudes, and perceptions (KAP) toward TB in several communities such as media exposure, [18][19][20] age, 19,20 education, 19,20 wealth index, 19 occupation, 18,19 and living area, 19,20 but investigations on the Indonesian general community are still scarce. Therefore, this study aimed to measure the KAP toward TB and their sociodemographic determinants among the Indonesian general community.…”
Section: Introductionmentioning
confidence: 99%
“…We have included various sociodemographic factors to evaluate the knowledge and attitude towards TB among the women. Several studies have reported that socioeconomic and demographic characteristics such as age, education, place of residence, wealth index, caste, religion, and geographic location play a role in TB transmission [10][11][12][13][14]. TB careseeking behaviour among people has been shown to be infuenced by their perceived knowledge about the signs and symptoms of TB.…”
Section: Introductionmentioning
confidence: 99%